Design and simulation of self-tuning PID-type fuzzy adaptive control for an expert HVAC system - Soyguder, Servet; Karakose, Mehmet; Alli, Hasan (Pergamon-Elsevier Science Ltd, 2009)
The modelling, numerical simulation and intelligent control of an expert HVAC (heating, ventilating and air-conditioning) system having two different zones with variable flow-rate were performed by considering the ambient temperature in this study. The sub-models of the system were obtained by deriving heat transfer equations of heat loss of two zones by conduction and convection, cooling unit and fan. All models of the variable flow-rate HVAC system were generated by using MATLAB/SIMULINK, and proportional-integral-derivative (PID) parameters were obtained by using Fuzzy sets. For comfortable of people the temperatures of the two different zones were decreased to 5 degrees C from the ambient temperature. The successful results were obtained by applying self-tuning proportional-integral-derivative (PID)-type fuzzy adaptive controller if comparing with the fuzzy PD-type and the classical PID controller. The obtained results were presented in a graphical form. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Self-tuning PID-type fuzzy adaptive controller; Fuzzy PD-type controller; Expert HVAC system; Intelligent control; Expert system